2012
DOI: 10.1128/aem.07402-11
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Contributions of the LiaS Histidine Kinase to the Innate Resistance of Listeria monocytogenes to Nisin, Cephalosporins, and Disinfectants

Abstract: ABSTRACTTheListeria monocytogenesLiaSR two-component system (2CS) encoded bylmo1021andlmo1022plays an important role in resistance to the food preservative nisin. A nonpolar deletion in the histidine kinase-encoding component (ΔliaS) resulted in a 4-fold increase in nisin resistance. In contrast, the ΔliaS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 47 publications
0
56
1
2
Order By: Relevance
“…The role of LiaRS in L. monocytogenes has been investigated (59,143,144). LiaRS-mediated signal transduction is also negatively regulated by LiaF, in a fashion similar to that described for B. subtilis (143).…”
Section: Liars and Liars-like Two-component Systemsmentioning
confidence: 93%
See 2 more Smart Citations
“…The role of LiaRS in L. monocytogenes has been investigated (59,143,144). LiaRS-mediated signal transduction is also negatively regulated by LiaF, in a fashion similar to that described for B. subtilis (143).…”
Section: Liars and Liars-like Two-component Systemsmentioning
confidence: 93%
“…In L. monocytogenes, however, the expression of 27 genes (143), including a PBP gene (57) and telA, which encodes a protein involved in toxic ion resistance (145), is also regulated. Collins et al (144) reported that a ⌬liaS strain grew more successfully than the corresponding wild type in the presence of nisin. A mutant lacking another histidine kinase, the ⌬lisK mutant, which also has a nisin resistance phenotype, was previously reported to alter liaS and PBP expression.…”
Section: Liars and Liars-like Two-component Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, future effectiveness of antimicrobial therapy is somewhat in doubt since various microorganisms are becoming more resistant to the existing antimicrobial agents [1][2][3][4][5][6] . Therefore, it is the responsibility of scientists to work hard and to find out environment friendly active compounds which can be used in this struggling.…”
Section: Oriental Journal Of Chemistrymentioning
confidence: 99%
“…These harmful microorganisms can be major source of food toxi-infection leading to different human diseases. For instance Salmonella and Listeria species, very resistant mircroorganisms at different conditions used for food preservation, can lead to salmonellose and listeriose, two known human fatal diseases [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%